The 'crisis' in defined benefit corporate pension liabilities. Part II: current solutions and future prospects - Clark, G; Monk, A (Palgrave Macmillan, 2007)
Once an integral component of company-sponsored compensation schemes in many Western economies, private defined benefit (DB) pensions are in decline. For many, DB schemes (and their related healthcare liabilities, depending on the jurisdiction) have hobbled the financial wellbeing of plan sponsors and even whole sectors of industry. If a constraint on shareholder value in the short term, these schemes threaten long-term corporate survival in the emerging global economy. While there remains considerable debate over the ability of financial markets to adequately price DB liabilities, there is a growing industry devoted to estimating their long-term risks with respect to longevity, inflation and cost. In part I of this two-part paper, we surveyed the nature and significance of the problem, focusing upon the UK and the US private employer-sponsored plans. We suggested that the 'crisis' was apparent, for those willing to look, a decade ago. Its significance was papered over by the 1990s stock market bubble and high interest rates but has returned through what many analysts identify as a 'perfect storm'. Having documented the nature and scope of the 'perfect storm', we now evaluate in part II the proffered solutions to the crisis, such as financial engineering, government intervention and private sector negotiation. In the final sections of the paper, we set out the principles that should guide the design of new kinds of employer-sponsored plans noting that if, as suggested by many experts, Western economies are entering an era of increasing labour shortage, private pensions will continue to have an important role in managing human capital.